A state of art of review on interactions between energy performance and indoor environment quality in Passive House buildings. (May 2017) - Wang, Yang; Kuckelkorn, Jens; Zhao, Fu-Yun; Spliethoff, Hartmut; Lang, Werner
Abstract: The building sector accounts for significant portion of total final energy use in most countries. One way to reduce significantly building energy consumption is to adopt energy efficiency technologies and strategies. Due to environmental concerns and high cost of energy in recent years there has been a renewed interest in building energy efficiency. Passive House (PH) standard provides a cost-efficient way of minimizing energy demand of buildings in accordance with global principle of sustainability. However, it is ongoing challenge to improve building energy efficiency without compromising indoor environmental quality. The objective of this paper is to review the interactions between energy performance and indoor environment quality in buildings with PH standard, considering parametric sensitivity study including effects of diverse parameters on PH building performance. Passive House technologies including heat and cooling recovery ventilation, pre heating/cooling fresh air, pre-ventilation and passive cooling are presented considering different weather conditions. Thermal comfort represented by recommended thermal range and comfort zone and indoor air quality indicated by CO2 concentration have been numerically and experimentally analysed. The simulation and measurement results illuminate that it is possible to realize energy efficiency and favourable indoor environment in PH buildings at the same time. Highlights: First review on interaction between energy performance and indoor environment in PH. Various technologies for PH investigated via simulation/monitoring/measurement. Evaluation on PH performance in different seasons also including transitional seasons. Energy conservation ratio correlated by heat recovery efficiency and outdoor/indoor air. Parametric sensitivity analysis including diverse effects on PH building performance.